QUANTIFYING RIVER ACCRETION IN THE UPPER RIO GRANDE GORGE, NEW MEXICO, BY USING AN ACOUSTIC DOPPLER CURRENT PROFILER. (2nd September 2011) - Kinzli, K.‐D.; Shafike, N.; Bauer, P.; Lundahl, A.; Schmidt‐Petersen, R.; Harris, S.; Lewis, G.; Johnson, P.; Timmons, M.
ABSTRACT The section of the upper Rio Grande in New Mexico is important to downstream water management and the administration of water rights. It has long been believed that this remote reach of the Rio Grande is characterized by significant groundwater accretions, which contribute to water available for downstream uses. This study focused on the uppermost 30 miles of the Rio Grande in New Mexico seeking to establish locations of groundwater accretions in the reach and document magnitude of gain. In order to quantify the accretion of the upper Rio Grande, an expedition using inflatable kayaks, an acoustic Doppler current profiler (ADCP) and an electromagnetic meter was carried out in the fall of 2008 when natural surface flow was low. The study area covered a stretch of 31 miles. The expedition was able to determine that the total accretion of this stretch of the Rio Grande was 22 ft3s−1 with an average accretion rate of 0.73 ft3s−1 mile−1. Most of the reach exhibited minimal gain or loss, and most of the accretion was centred in Sunshine Valley. One of the most significant results was encountering a large artesian, subaqueous spring, which might be the largest documented spring in New Mexico and contributes nearly 50% of the accretion in the reach. The study was also able to characterize the exact locations of other significant groundwater inputs. In addition to quantifying the accretion of part of the upper Rio Grande, the study provides the framework for using advanced technology in the form of an ADCP to determine river accretions in remote locations. ADCPs offer the benefit of reducing measurement time and measurement error, collect high‐resolution data and are non‐intrusive. Overall, the use of ADCP technology to determine river accretion offers an improvement over traditional methods, and it is the hope of the authors that this technology is utilized for river accretion studies in the future. Copyright © 2011 John Wiley & Sons, Ltd.